Pelatihan Pendampingan Implementasi STEM untuk Meningkatkan Kualitas Pembelajaran IPA Bagi Kelompok Kerja Guru SD - Yenni Fitra Surya; Sumianto; Al Amin; Armiswati (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The objectives of this community service are: (1) To provide knowledge to elementary school teachers related to the STEAM (Science, Technology, Engineering, Arts and Mathematics) learning approach; (2) To provide knowledge to elementary school teachers related to integration in mathematics learning; (3) To provide skills to elementary school teachers related to the STEAM learning approach; (4) To instill values ​​and attitudes to elementary school teachers related to the STEAM learning approach. The training method for the STEAM learning approach to SDN 192 teachers is through: (1) Expository; (2) Questions and Answers; (3) Discussion; (4) Demonstration; (5) Focus Group Discussion (FGD); (6) Project method. The instruments used in community service are: (1) Power Point; (2) Copy of STEAM learning approach materials;. Data collection techniques are through interviews, observations and documentation. Data are analyzed qualitatively. The conclusion in this community service is as follows: (1) Elementary school teachers have knowledge related to the STEAM (Science, Technology, Engineering, Arts and Mathematics) learning approach; (2) Elementary school teachers have values ​​and attitudes related to the STEAM learning approach; (4) Elementary school teachers have values ​​and attitudes that can be instilled in elementary school children related to the STEAM learning approach.